Evolution of life history strategies in Lophoziaceae - Manyanga, Phelex (Department of Biological Sciences, 2024)
This study used data from literature and data from the field to analyse the patterns of variation in life history characters among members of the liverwort family Lophoziaceae. A combination of Principal Component and Cluster analyses was used to analyse data from literature in testing for recurrent suites of life history variation among species of the family. Data from literature were also used to examine the relationship between mode of reproduction and reproductive system (sexuality) and between diaspore (spore or gemma) frequency and sexuality. Data from the field were used to establish diaspore (spore and gemma) sizes and their production per capsule or shoot and to test for relationships between diaspore size and production per shoot/capsule and also between diaspore sizes and proportion of germination. The study showed the existence of recurrent suites of life history variation in the family. The clusters produced were shown to be independent of the species' phylogeny, but were closely related to the habitat parameters such as nature of substrate, duration of habitat availability and moisture condition. The study also shows dominance of dioicous species in the family, with about 90% of the studied species being dioicous. There is a statistically significant relationship between reproductive system and sporophyte frequency; monoicous species produce sporophytes more frequently than dioicous species. A negative relationship was shown to generally exist between spore size and number of spores produced per capsule at both species and population levels. However, no relationship could be established between gemma size and the number of gemmae produced per shoot. For two of the studied species, L. ciliata and L. /ongiflora, there was a general positive relationship between spore size and proportion of germination, with bigger spores having higher germination proportions. L ventricosa showed a negative relationship between spore size and germinability.